2003
DOI: 10.1121/1.1554696
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and mechanical response of reservoir rocks under variable saturation and effective pressure

Abstract: We investigate the acoustic and mechanical properties of a reservoir sandstone saturated by two immiscible hydrocarbon fluids, under different saturations and pressure conditions. The modeling of static and dynamic deformation processes in porous rocks saturated by immiscible fluids depends on many parameters such as, for instance, porosity, permeability, pore fluid, fluid saturation, fluid pressures, capillary pressure, and effective stress. We use a formulation based on an extension of Biot's theory, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…A plane-wave analysis predicts one shear (S-wave) and three compressional waves: a fast P-wave corresponding to the motion in phase of the solid and fluid phases, and two slow P waves associated with motions out of phase of the two fluids. An extension of this model to include in situ conditions of the single phases and viscoelasticity is given inRavazzoli et al (2003) andRavazzoli and Santos (2005), with a parametric analysis of the influence of effective pressure, abnormal pore pressure and saturation on the phase velocities and quality factors of the different waves.The first numerical evidence of the presence of a second slow wave in porous solids saturated by immiscible fluids is presented inSantos et al (2002) and later inSantos et al (2004b). It is shown that the second slow wave can be detected at ultrasonic frequencies, while at low frequencies is a source of attenuation of the fast waves (the mesoscopic loss).Partially frozen porous media and shaley sandstones are particular cases of fluid saturated porous media when the solid matrix is composed of two weakly-coupled solids Leclaire et al (1994).…”
mentioning
confidence: 99%
“…A plane-wave analysis predicts one shear (S-wave) and three compressional waves: a fast P-wave corresponding to the motion in phase of the solid and fluid phases, and two slow P waves associated with motions out of phase of the two fluids. An extension of this model to include in situ conditions of the single phases and viscoelasticity is given inRavazzoli et al (2003) andRavazzoli and Santos (2005), with a parametric analysis of the influence of effective pressure, abnormal pore pressure and saturation on the phase velocities and quality factors of the different waves.The first numerical evidence of the presence of a second slow wave in porous solids saturated by immiscible fluids is presented inSantos et al (2002) and later inSantos et al (2004b). It is shown that the second slow wave can be detected at ultrasonic frequencies, while at low frequencies is a source of attenuation of the fast waves (the mesoscopic loss).Partially frozen porous media and shaley sandstones are particular cases of fluid saturated porous media when the solid matrix is composed of two weakly-coupled solids Leclaire et al (1994).…”
mentioning
confidence: 99%
“…From the known values of the velocities of propagation of elastic waves in rocks and the density of these rocks, it is possible to calculate the values of such elastic moduli as Young's modulus, Poisson's ratio, shear modulus, and bulk modulus [19] [20]. A decrease in reservoir pressure during field development will not only lead to a decrease in the porosity value but will also reduce the gas permeability values [21] [22]. The performed experimental studies made it possible to obtain the dependence of the gas permeability coefficient (K) on P eff (Fig.…”
Section: Fig7:change In the Velocity Of Lateral Waves With An Increamentioning
confidence: 99%
“…Our model is based on a generalization of Biot's theory [5][6][7] for porous rocks saturated by two immiscible fluids [36,39,40]. It takes into account the existence of capillary forces at the pore scale, assuming that each fluid phase has a continuous distribution within the tortuous pore space and that both fluids can flow (funicular saturation regime).…”
Section: Introductionmentioning
confidence: 99%